DETERMINASI KONSUMSI RUMAH TANGGA MISKIN: STUDI DI KELURAHAN MATA ALLO, KABUPATEN GOWA - Asriati (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2024)
This study aims to analyze the influence of income, family dependents, and household head economic activities on the consumption expenditure of poor households in Mata Allo Village, Gowa Regency. This research employed a quantitative approach with a survey method, involving 81 respondents selected through simple random sampling. Data were analyzed using multiple linear regression to determine the significant effects of independent variables on poor household consumption expenditure. The results revealed that all three independent variables positively and significantly affect household consumption expenditure. Income was the dominant factor with the highest beta coefficient (0.424), followed by household head economic activities (0.330) and family dependents (0.251). These findings support Keynes’ consumption theory and Friedman’s permanent income theory, emphasizing the critical role of income and economic stability in household consumption patterns. This study recommends economic empowerment policies through income enhancement, social protection, and job diversification to improve the welfare of poor households.